2013
DOI: 10.1002/chem.201302189
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectrum of the Si3H8+ Cation: Evidence for a Bridged Isomer with an Asymmetric Three‐Center Two‐Electron SiHSi Bond

Abstract: The IR spectrum of Si3H8(+) ions produced in a supersonic plasma molecular beam expansion of SiH4, He, and Ar is inferred from photodissociation of cold Si3H8(+)-Ar complexes. Vibrational analysis of the spectrum is consistent with a Si3H8(+) structure (2(+)) obtained by a barrierless addition reaction of SiH4 to the disilene ion (H2Si=SiH2(+)) in the silane plasma. In this structure, one of the electronegative H atoms of SiH4 donates electron density into the partially filled electrophilic π orbital of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 104 publications
3
19
0
1
Order By: Relevance
“…For this purpose, the octopole is filled with N 2 up to 10 À5 mbar, which results in collisions with B10 eV collision energy in the laboratory frame. Recent applications of this IRPD approach of tagged ions in our laboratory include hydrocarbon ions, [48][49][50][51][52][53][54][55][56][57] silicon-containing ions, [58][59][60] and biological molecules and their hydrates. [61][62][63][64][65][66] DFT calculations 67 are carried out at the B3LYP-D3/aug-cc-pVTZ level to determine the geometric, vibrational, and energetic properties of the H + PEA conformers and their H + PEA-Rg n clusters.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…For this purpose, the octopole is filled with N 2 up to 10 À5 mbar, which results in collisions with B10 eV collision energy in the laboratory frame. Recent applications of this IRPD approach of tagged ions in our laboratory include hydrocarbon ions, [48][49][50][51][52][53][54][55][56][57] silicon-containing ions, [58][59][60] and biological molecules and their hydrates. [61][62][63][64][65][66] DFT calculations 67 are carried out at the B3LYP-D3/aug-cc-pVTZ level to determine the geometric, vibrational, and energetic properties of the H + PEA conformers and their H + PEA-Rg n clusters.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Hydrogen termination is an effective means of passivation and stabilization of silicon clusters. [12][13][14][15][16][17] There is also significant interest in SiO 2 matrices with embedded nanocrystalline silicon. [18][19][20] For small isolated Si n clusters, dissociative adsorption of dioxygen molecules has a significant impact on their geometry and electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…George et al [69] identified a hydrogen bridged trisilane cation structure H 3 SiAHASiH 2 ASiH 3 + whose energy is only a few kJ/mol higher than the classical trisilane cation SiH 3 ASiH 2 ASiH 3 + . The barrier between the two isomers is only 0.8 eV [69].…”
Section: Considerations On Fragmentation Mechanismsmentioning
confidence: 99%
“…George et al [69] identified a hydrogen bridged trisilane cation structure H 3 SiAHASiH 2 ASiH 3 + whose energy is only a few kJ/mol higher than the classical trisilane cation SiH 3 ASiH 2 ASiH 3 + . The barrier between the two isomers is only 0.8 eV [69]. Tarczay and co-authors [55] have therefore recently suggested that the fragmentation of silanes during vacuum ultra-violet (VUV) photoionization goes via the hydrogen bridged structure.…”
Section: Considerations On Fragmentation Mechanismsmentioning
confidence: 99%